MANAGEMENT OF SCLEROTAIL WILT DISEASE OF BETELVINE IN MADHYA PRADESH - ASHISH KUMAR TRIPATHI (The Bioscan, 2015)
Stem rot or basal rot of Betelvine (Piper betle L.) caused by Sclerotium rolfsii is most destructive disease in Madhya Pradesh. The results of research as well as on farm trails revealed that the Sclerotial wilt disease significantly controlled by seed treatment and soil drenching with Hexaconozole (4.5 %), Trichoderma viride (4.6 %) and Carboxin + Thiram (4.8 %) in comparison to control (21.7%). In on farm research trails, sclerotial wilt disease incidence reduced 84.6 % by seed + soil drenching with Hexaconozole 0.1 per cent.